ORGANISING EFFECTIVE INTERACTION OF MANAGERS OF ARCHITECTURAL AND CONSTRUCTION COMPANIES WITH CLIENTS BASED ON THE THEORY OF NON-VIOLENT COMMUNICATION - Руслан Кубанов; Дмитро Макатьора; Ярослав Кушик-Стрельніков (Економіка та суспільство)
Based on the theory of non-violent communication, the article deals with the problem of organising effective interaction of managers of architectural and construction companies with clients. The authors emphasise that since clients have high demands and expectations that need to be skilfully taken into account, ensuring quality communication with clients is a key task for modern managers in this field. The article examines the current trends and problems that the managers of architectural and construction companies have to face in the process of interaction with their clients. Key issues include ineffective management of client requirements, failure to meet agreements and deadlines, inadequate communication support and inadequate response to changing client needs. It is noted that an important role in solving these problems is played by the ability of managers to organise high quality communication that gives customers a sense of attention, understanding and trust. The theory of non-violent communication, developed by the psychologist Marshall Rosenberg, is described in some detail. It is a universal model for building effective relationships in many areas of life, based on empathy, acceptance of the other person and compassion. The key components of non-violent communication are analysed, such as non-judgmental observation, distinction between feelings and thoughts, understanding of the client’s wishes and the ability to formulate constructive requests. Examples are given of how to apply these principles in practice when dealing with architectural and construction managers and clients. The importance of using the theory of non-violent communication to build trust, avoid conflict, enhance reputation and achieve positive business results is demonstrated. Specific recommendations, including conducting training, creating internal communication standards, implementing a customer feedback system, and developing active listening and empathy skills, are provided to improve managers’ communication practices. An algorithm for effective problem solving is presented, with special attention to the specifics of using non-violent communication when working with clients in conflict.